Sifat dan Jadwal Pengeringan Lima Jenis Kayu Papua Barat The Drying Properties and Schedules of Five Wood Species from West Papua - Efrida Basri; R.G.N. Triantoro; Wahyudi Wahyudi (Jurnal Ilmu dan Teknologi Kayu Tropis, 2007)
This study was aimed to investigate the drying properties and schedules of five wood species from West Papua, i.e. Tarua (Antiaris toxicaria), Sonokembang (Pterocarpus indicus), Merbau (Intsia bijuga), Mangium (Acacia mangium) and Mendarahan (Myristica longipes). Modified Terazawa Method was used for the drying properties tests. The physical properties measured were airdry density and green moisture content. The determination of drying schedule was carried out by examining the wood drying properties at 100ºC.Results indicated that the drying properties were not affected by density but by wood anatomical structure. One of 5 wood species (i.e. Merbau wood) was resistant to high temperature although its density is the highest. Based on drying properties, all samples of 5 wood species could be classified into 5 drying schedule groups.